1997
DOI: 10.1161/01.cir.95.8.2075
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical Septal Reduction for Hypertrophic Obstructive Cardiomyopathy

Abstract: Nonsurgical septal reduction significantly reduces left ventricular outflow tract obstruction and improves symptoms in some patients with hypertrophic obstructive cardiomyopathy. The technique may provide an alternative to surgical myomectomy in selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
143
0
12

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 266 publications
(161 citation statements)
references
References 13 publications
6
143
0
12
Order By: Relevance
“…The size of septal myocardial infarction was small and the left ventricular function was preserved. There have been several reports (6)(7)(8) on the complications of the procedure, such as ventricular arrhythmia including ventricular fibrillation. Seggewiss et al (7) reported complete heart block in 20% of the patients requiring permanent pace-maker implantation and an 86-year-old womandied with ventricular fibrillation after the successful intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of septal myocardial infarction was small and the left ventricular function was preserved. There have been several reports (6)(7)(8) on the complications of the procedure, such as ventricular arrhythmia including ventricular fibrillation. Seggewiss et al (7) reported complete heart block in 20% of the patients requiring permanent pace-maker implantation and an 86-year-old womandied with ventricular fibrillation after the successful intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Seggewiss et al (7) reported complete heart block in 20% of the patients requiring permanent pace-maker implantation and an 86-year-old womandied with ventricular fibrillation after the successful intervention. Transient occlusion of the left anterior descending artery due to alcohol leaking down the main lumen of the artery was reported (6). The angioplasty balloon must be kept inflated in the septal artery at least for a few minutes after the infusion of absolute alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Mais recentemente, foram relatados resultados preliminares da aplicação de técnica intervencionista percutânea, para produção de infarto septal e, conseqüente, redução do fenômeno obstrutivo sistólico na cardiomiopatia hipertrófica 17,18 . Esses relatos, pertinentes a 18 pacientes estudados na Europa, foram reproduzidos em centro norte-americano, em outro grupo de 18 casos similares 19 .…”
Section: Discussionunclassified
“…Análise de 18 casos submetidos a esse tratamento demonstrou significativa redução da obstrução da via de saída do VE, havendo referência a um caso que apresentou episódios de taquicardia ventricular, elevação do segmento ST do ECG, acentuada elevação da enzima creatinoquinase (14.960UI) e oclusão transitória da artéria interventricular anterior. Essas complicações foram interpretadas como secundárias ao extravasamento da solução alcoólica para a artéria interventricular anterior 12 .…”
Section: Comentáriosunclassified